Improve Literacy Learning through Using Storytelling: Survey of Literature - Maddumage, Dr. Kumudini (International Journal on Integrated Education, 2023)
Storytelling is one of the most important forms of human communication in the development of language skills. Substantial literature is available on story telling as an effective pedagogical tool in developing language skills. According to literature effectiveness of storytelling depends on the factors such as fun, joy, engaging, highly memorable and enhancing learners’ interest in listening to stories, as well as in speaking, writing and reading. As a language teaching tool, storytelling has been identified as the most effective language teaching method than the traditional teaching materials such as textbooks. The aim of this literature review is to provide definitions on what is storytelling and provide an overview about what research says about how storytelling helps with improving reading and writing skills of young children. This paper will help teachers to understand the role of storytelling in a language classroom and improve their language teaching skills.